2019
DOI: 10.1093/labmed/lmy083
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Monocyte-Plus-Lymphocyte Ratio as a Potential Marker for Discriminating Pulmonary Tuberculosis from Nontuberculosis Infectious Lung Diseases

Abstract: Objective To determine whether NMLR has more statistical strength than NLR in discriminating TB from non-TB infectious lung diseases. Methods Among patients who underwent 3 or more TB culture tests with molecular study between January 2016 and December 2017, 110 patients with TB, and 159 patients diagnosed with non-TB infectious lung diseases were enrolled. The original complete blood count (CBC) parameters and modified CBC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 19 publications
5
36
0
Order By: Relevance
“…NLR is an indicator of systemic inflammation [28], mainly seen in tumor-related diseases, autoimmune diseases, bacterial infectious pneumonia and tuberculosis [29][30][31][32]. It was reported that COVID-19 infection-triggered inflammation increased NLR and the increase in NLR was significantly associated with poor clinical outcomes of COVID-19 patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…NLR is an indicator of systemic inflammation [28], mainly seen in tumor-related diseases, autoimmune diseases, bacterial infectious pneumonia and tuberculosis [29][30][31][32]. It was reported that COVID-19 infection-triggered inflammation increased NLR and the increase in NLR was significantly associated with poor clinical outcomes of COVID-19 patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…A number of prior studies have evaluated CBC-derived ratios (MLR, NLR, and/or PLR) in the context of symptomatic TB disease, speci cally related to either predicting subsequent TB disease development, diagnosing TB disease, or monitoring disease response to antimicrobial therapy (5)(6)(7)(8)(9)(10)(11)(12)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). These studies were heterogeneous with respect to the geographic region from which participants originated, presence of comorbidities (such as HIV), age, concurrent use of TB therapy, and choice of control groups, making comparisons challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Third, because MLR, NLR, and PLR are hypothesized to represent non-speci c markers of in ammation, inclusion of other controls groups, such as individuals with other chronic infections (e.g., HIV) or chronic in ammatory conditions, would have been potentially bene cial. However, our study was designed primarily as a TB vaccine trial and therefore did not include such groups, although others have considered similar controls in prior studies (18)(19)(20)23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CBC ratios described here are hypothesized to represent markers of non-specific inflammation, and have been evaluated in the context of TB disease [5][6][7][8][9][10][11][12][15][16][17][18][19][20][21][22][23][24][25], malignancy [26][27][28][29][30], and several other conditions that are hypothesized to have a pro-inflammatory component [31][32][33]. Through the analysis of paired CBC and IGRA assays, we are able to report on the utility of baseline MLR, NLR, and PLR, as well as other CBC components, for predicting future development of asymptomatic TB infection and on the effect of incident TB infection on concurrent CBC values.…”
Section: Introductionmentioning
confidence: 99%